What is the effect of emotional processing on depression? A longitudinal study - Pinheiro, Patrícia (2021)
Emotional processing is an empirically established predictor of pre-post therapy improvement in depression. However, its relationship to symptom alleviation over time requires clarification. To clarify the contribution of emotional processing to gradual symptom improvement, we explored both (1) the effect of emotional processing on pre-post therapy changes in depressive symptoms (final outcome) and (2) its association with the intensity of clinical symptoms across sessions (session-by-session outcome). These relationships were estimated in a sample of 50 depressed clients treated with cognitive-behavioral therapy (CBT) or emotion-focused therapy (EFT). Emotional processing was measured by the Experiencing Scale during Emotion Episodes in five sessions taken across therapy. As expected, we found that a greater increase in emotional processing during treatment predicted a greater pre-post therapy improvement in depressive symptoms. Higher levels of emotional processing predicted next-session lower intensity on clinical symptoms, but the intensity of symptoms contributed to explaining the subsequent level of emotional processing achieved. Our observations suggest that clients' capabilities to process their emotions may both facilitate and be promoted by gradual improvement in symptoms. These results suggest the reciprocal predictive influence of emotional processing and symptoms on the therapeutic change in depression.